2014
DOI: 10.1002/sia.5550
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulations of sputtering and fragment formation during keV C60 bombardment of octane and β‐carotene

Abstract: Molecular dynamics computer simulations are used to investigate material ejection and fragment formation during keV C 60 bombardment of organic solids composed from small (octane) and medium ( β-carotene)-sized organic molecules. Both systems are found to sputter efficiently. For the octane system, material removal occurs predominantly by ejection of intact molecules, whereas fragment emission is a main ejection channel for β-carotene. A difference in the molecular dimensions is proposed to explain this observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…It appeared later that these effects were both influenced by the mass of the projectile atoms . Recently, Postawa et al also studied the sputtering of organic solids with two different molecular weights, n -octane (114 amu) and β-carotene (537 amu), and they found almost no difference of sputtered quantities . This observation seemed at odds with some of the experimental SIMS literature and with our own simulations comparing kDa chains with virtually infinite polymers .…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations
“…It appeared later that these effects were both influenced by the mass of the projectile atoms . Recently, Postawa et al also studied the sputtering of organic solids with two different molecular weights, n -octane (114 amu) and β-carotene (537 amu), and they found almost no difference of sputtered quantities . This observation seemed at odds with some of the experimental SIMS literature and with our own simulations comparing kDa chains with virtually infinite polymers .…”
Section: Introductionmentioning
confidence: 65%
“…A recent atomistic MD study of C 60 bombardment of organic materials investigated the molecular size effect to some extent by comparing the sputtering of octane and β-carotene from their molecular solids. 38 Octane is about two times smaller than PE282 while β-carotene is about 2 times larger. Despite the differences in the models and in the samples, a similar conclusion was drawn in their study, i.e., that the total sputter yield was comparable for the two samples at a given projectile energy and that the ratio of intact molecules to fragments was larger for the smaller molecules.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The simulations have been applied on more complicated materials including organic molecules by development of interatomic potentials [50][51][52]. The analysis on chemical components revealed that cluster impact shows less fragmentation in sputtering and crosslinking in the target, which probes the advantages in precise measurement and depth profiling of XPS and SIMS of organic materials.…”
Section: Computer Simulation For Cluster Impactsmentioning
confidence: 99%